Characterization of a large animal aerosol exposure system for aerosolizing four strains of Burkholderia pseudomallei. (June 2015) - Barnewall, Roy E.; Benson, Eric M.; Brown, Megan A.; Fisher, David A.; Lindsay, Amber S.; Simmons, Amy A.; Anderson, Michael S.
Abstract: Burkholderia pseudomallei is a Gram-negative, motile, non-spore-forming, aerobic bacteria found in contaminated water, soil, and on market produce. It is the causative agent of melioidosis, an infectious disease endemic to Southeast Asia and northern Australia, and may occur in other tropical and subtropical regions. The spray factor (SF) for four strains of B. pseudomallei and the reproducibility of a large animal exposure system were evaluated. The SF value is the ratio of aerosol concentration to the starting concentration of the nebulized material (spray factor=Conc aerosol /Conc neb ). This relationship provides an indication of the aerosol system to deliver a consistent B. pseudomallei aerosol concentration. From the data, a SF value was determined that can be used as a measure of aerosol system reproducibility and for dose predictions by determining the degree of variability in the predicted Intraday and Interday SF variability. Based on the data between test days, the aerosol system is expected to produce a mean measured dosage within the range of 0.67 to 1.5 times (95 percent probability) the mean estimated/targeted dosage for a future test day with ten aerosol runs at a particular targeted nebulizer concentration. Additionally, for the variability within a ten run test day at a targeted nebulizer concentration, the ratio of the maximum-to-minimum aerosol concentration should be no greater than 3.7-fold (95 percent probability). The inhalation delivery of these four B. pseudomallei strains using the aerosol system is anticipated to provide consistent and reproducible dosages within a test day, between test days, and between studies. Highlights: An aerosol system was characterized. Four bacterial strains were examined. Inter-Day and Intra-Day variability was examined. Variability examined in terms of spray factor value. The variability and aerosol system were highly consistent from day-to-day (Inter-Day) and within a day (Intra-Day).